Producing Referring Expressions in Identification Tasks and Route Directions: What's the Difference?. Issue 2 (17th February 2019) - Baltaretu, Adriana; Krahmer, Emiel; Maes, Alfons
ABSTRACT: Although communicative purposes are an important element in language production, few studies investigate the extent to which they might affect referential choices. In this study we contrast two tasks with different purposes: identification and route directions giving. In Experiment 1 speakers referred to a target building nearby or further away so their addressee would distinguish it from other buildings (identification) or give route directions and use the same building as a landmark (instructions). Our results showed that irrespective of the speaker's purposes, referring expressions consisted of the same types of attributes, yet the attribute frequency and formulation differed. In the identification task the referring expressions were longer and contained more locative and more postnominal modifiers. In addition, referential choices were influenced by the visual distance between the speaker and the target: When speakers observed the target from afar, their references were longer and contained more often locative modifiers. In Experiment 2 a different group of participants had to evaluate references produced in Experiment 1 while assessing descriptions of objects or descriptions of objects extracted from route directions. Neither task, distance, nor the length of the phrases influenced their choice, indicating that addressees consider references produced in both conditions equally adequate in both uses.